2018
DOI: 10.7717/peerj.4655
|View full text |Cite
|
Sign up to set email alerts
|

Host and symbiont genetic contributions to fitness in aTrichogramma–Wolbachiasymbiosis

Abstract: The fitness effects associated with Wolbachia infection have wide-ranging ecological and evolutionary consequences for host species. How these effects are modulated by the relative influence of host and Wolbachia genomes has been described as a balancing act of genomic cooperation and conflict. For vertically transmitted symbionts, like cytoplasmic Wolbachia, concordant host–symbiont fitness interests would seem to select for genomic cooperation. However, Wolbachia’s ability to manipulate host reproductive sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Similar results have been obtained in Nasonia vitripennis , when wasps infected with two Wolbachia strains ( w Av and w Bv) appeared to produce more offspring when in different genetic backgrounds to the strains used for comparison, whereas no positive fitness effects were found once host genetic background was controlled (Bordenstein and Werren, ). Fitness variation, including fecundity and survival, will often largely represent a function of host genetic background (Russell et al ., ). The costs we have detected for the Wolbachia and Spiroplasma contrast with the effects of a Wolbachia and Spiroplasma co‐infection in D. melanogaster , where there is no evidence of any benefits or costs when compared with single infections (Montenegro et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Similar results have been obtained in Nasonia vitripennis , when wasps infected with two Wolbachia strains ( w Av and w Bv) appeared to produce more offspring when in different genetic backgrounds to the strains used for comparison, whereas no positive fitness effects were found once host genetic background was controlled (Bordenstein and Werren, ). Fitness variation, including fecundity and survival, will often largely represent a function of host genetic background (Russell et al ., ). The costs we have detected for the Wolbachia and Spiroplasma contrast with the effects of a Wolbachia and Spiroplasma co‐infection in D. melanogaster , where there is no evidence of any benefits or costs when compared with single infections (Montenegro et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…insecticola were reared on wheat seedlings in Petri dishes as the Regiella -infected strains, and the other thirty aphid clones naturally lacking any known facultative endosymbionts were reared as Regiella -free strains. Previous studies suggested that the effects of endosymbionts on host fitness might be dependent on host and symbiont genotype or an interaction between the two 45,46 . Therefore, the genotype of each aphid clone used in this study was examined using PCR based on six microsatellite loci, S49, Sm10, Sm12, Sav1, Sav2 and Sav4 47,48 .…”
Section: Methodsmentioning
confidence: 99%
“…(ii) It could be due to different Wolbachia/host combinations. Documents have revealed that different Wolbachia strains could induce distinct phenotypes in one host, and one Wolbachia strain may have various effects on different hosts (Dean, 2006;Chafee et al, 2011;Russell et al, 2018). In their case, wVulC Wolbachia is pathogenic and over-replicates reducing the lifespan of its host.…”
Section: Effect Of Wolbachia On Learning and Memory Capacity (Lmc) Inmentioning
confidence: 99%